An evaluation of interest deduction limitations to counter base erosion in South Africa - Pieter Van der Zwan; Danie Schutte; Waldo Krugell; Joel Seshabela; Hayley Reynolds; Londiwe Khoza (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper aims to describe funding structures of companies liable for tax in South Africa and how this relates to other characteristics, including ownership, of the companies. The research that the paper reports on was performed as descriptive analyses. While no clear indication of a preference for debt could be identified, the results showed that the mean net interest coverage ratio for certain foreign-owned entities differed significantly from that of domestically owned entities. This may be evidence of profit-shifting activities. The results highlight trends in interest coverages ratios that may be of relevance for future legislative developments.
Keywords: H20; H25; H26; 330; interest deduction limitation; interest coverage ratio; profit shifting; South Africa